2016
DOI: 10.1111/gtc.12370
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal knockdown of dok‐7 gene expression in mice causes structural defects in neuromuscular synapses and myasthenic pathology

Abstract: The neuromuscular junction (NMJ) is a synapse between a motor neuron and skeletal muscle and is required for muscle contraction. The formation and maintenance of NMJs are governed by the muscle-specific receptor tyrosine kinase MuSK. We previously showed that the muscle cytoplasmic protein Dok-7 is an essential activator of MuSK. Indeed, mice lacking either Dok-7 or MuSK form no NMJs, and defects in the human DOK7 gene underlie a congenital myasthenic syndrome (an NMJ disorder). However, it remains unproven wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The relatively short exposure duration of the zebrafish to salbutamol and forskolin may further explain why only a partial rescue of the phenotype was observed in both models. In addition, patients with CMS due to DOK7 mutations frequently present after infancy or in early adulthood ( 38 ), and postnatal knockdown of Dok-7 gene expression has been shown to cause CMS in mice ( 39 ), indicating a further role for Dok-7-mediated activation of MuSK in postnatal NMJ maintenance. Therefore, it is possible that the improvement seen in β-agonist-treated CMS patients is due to an additional role they play in NMJ homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively short exposure duration of the zebrafish to salbutamol and forskolin may further explain why only a partial rescue of the phenotype was observed in both models. In addition, patients with CMS due to DOK7 mutations frequently present after infancy or in early adulthood ( 38 ), and postnatal knockdown of Dok-7 gene expression has been shown to cause CMS in mice ( 39 ), indicating a further role for Dok-7-mediated activation of MuSK in postnatal NMJ maintenance. Therefore, it is possible that the improvement seen in β-agonist-treated CMS patients is due to an additional role they play in NMJ homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…These examples highlight the interdependence between all three cellular components of the NMJ, and roles of synapse-associated molecules in the maintenance and repair of adult NMJs. In this regard, studies over the last few years have shown that synaptic molecules agrin, Lrp4, the muscle-specific kinase (MuSK) receptor, and Dok7 remain essential at adult NMJs [6164]. For example, deletion of agrin in a subset of adult motor neurons causes the disintegration of the postsynapse and degeneration of motor axons [63].…”
Section: Lifestyle and Molecular Factors That Preserve The Nmj Intmentioning
confidence: 99%
“…For example, deletion of agrin in a subset of adult motor neurons causes the disintegration of the postsynapse and degeneration of motor axons [63]. Likewise, adult NMJs degenerate in the absence of LRP4, MuSK, or Dok7 [61,62,64]. Thus, molecules required for the formation of the NMJ continue to play integral functions in adulthood.…”
Section: Lifestyle and Molecular Factors That Preserve The Nmj Intmentioning
confidence: 99%
“…Following a facial nerve crush injury protocol, we observed axonal degeneration and muscle fiber reinnervation similar to that described in the hind limb Tibialis anterior muscle after sciatic nerve crush injury (Magill et al, 2007 ). In the context of NMJ regeneration, several muscle proteins that play essential roles in the embryonic assembly have demonstrated a potentially key role on helping NMJ maintenance, such as LRP4 (Barik et al, 2014 ), Dok-7 (Eguchi et al, 2016 ), and rapsyn (Kong et al, 2004 ; Martínez-Martínez et al, 2009 ). Indeed, overexpression of a low copy number of MuSK partially rescues the NMJ degeneration that takes place at pre-symptomatic stages of Amyotrophic Lateral Sclerosis animal models (Pérez-Garcia and Burden, 2012 ).…”
Section: Discussionmentioning
confidence: 99%